Kompensasi dan kepuasan kerja terhadap niat keluar: Peran mediasi komitmen organisasional pada karyawan kedai kopi di Yogyakarta - Gustomo, Gayuh Ridho; Subiyanto, Didik; Yulianto, Eko (Nur Science Institute, 2025)
This study aims to determine the effects of compensation and job satisfaction on turnover intention, with organizational commitment as a moderating variable, among employees of Homwok Coffee in Yogyakarta. This research is a quantitative study using a non-probability sampling technique, specifically saturated sampling, in which all members of the population were included as the sample. The respondents in this study were 70 employees of Homwok Coffee Yogyakarta. Data analysis consisted of descriptive and inferential statistical analyses, including variance-based SEM and indicator and model fit tests. The results of the study show that compensation has a positive and significant effect on turnover intention, and that job satisfaction has a positive and significant effect on turnover intention. Compensation and job satisfaction have positive, significant effects on organizational commitment. Organizational commitment has a positive, significant effect on turnover intention. Furthermore, organizational commitment can function as a mediating variable in the relationship between compensation and turnover intention, as well as between job satisfaction and turnover intention. This research is expected to help business practitioners understand the extent to which compensation and job satisfaction influence organizational commitment, which, in turn, affects employees’ turnover intentions.